PROGRAM HEART OF BORNEO WWF DALAM PELESTARIAN HUTAN DI KALIMANTAN - Rangga Putra Firmansyah; Eko Priyo Purnomo; Aulia Nur Kasiwi; Delila Putri Sadayi (Lambung Mangkurat University-Indonesia, 2021)
This study aims to see how the programs of the Heart of Borneo (HoB) and the actions taken by the HoB in forest conservation in Kalimantan. Forest is an area that is overgrown with dense trees and as a place to live flora and fauna that live without human intervention. Forests are the key to the survival of creatures on earth, including humans, because they can affect many things that include life and sustainability. One organization that cares about forests is the World Wide Fund for Nature (WWF) and the organization formed by WWF to protect Kalimantan's forests is the Heart of Borneo. The purpose of the Heart of Borneo itself is to preserve and maintain the rainforest areas in Kalimantan for the welfare of present and future generations. The method used in this study is a descriptive qualitative research method in which the researcher seeks to describe a phenomenon, event, and event that is happening which is then described as there where the researcher tries to describe the Heart of Borneo program in Kalimantan. The results of this study indicate that forest destruction that occurred in Kalimantan is very worrying. The damage was caused by large-scale forest clearing wich changed its functions to the coal mining, the conversion of forest land to oil palm agriculture functions that damage the living ecosystem of flora and fauna. Previously, Kalimantan forest were very beneficial for human life and the flora fauna that live in it.Through the Heart of Borneo program, it seeks to protect the remaining forest in Kalimantan to remain sustainable and function properly